THE STANDPOINTS OF ATEITININKAI TO PRESERVE NATIONAL IDENTITY - Gedvilienė, Genutė; Šukys, Aurimas (Acta Paedagogica Vilnensia, 2007)
The problem of the national identity was very acute after the collapse of the soviet regime in Lithuania. This happened because it was not fully allowed to practise national virtues on official as well as on daily level during the soviet time. The „homo sovieticus“ species were artificially intruded into the consciousness of Lithuanian citizens. The period of last 15 years is still the time of searching for modern NATIONAL identity. One way migration from Lithuania to the Western World proves the fact that people do not really feel, what does it mean to be a Lithuanian nowadays. The experience of Ateitininkai in the West keeping the national identity alive could be a good outcome of the Lithuanian identity crisis today. Ateitininkai were an influential catholic youth organization that was established in 1911 in Lithuania. Part of them retreated to the West together with the first wave of Lithuanian emigrants of the Second World War. The same problem of national identity was very important and challenging to all of them. The organization, regenerated abroad, followed the ideas and principles of its predecessors. Ateitininkai actively cooperated in the creation of Lithuanian Diaspora, i.e. the World Lithuanian Community. They assumed the participation in this activity as direct duty arising out of their ideology. The members of „Ateitis“ federation considered Lithuanian Diaspora as their moral and cultural community. As an example of such community frequent references to Jewish Diaspora were indicated in the texts by Ateitininkai. The conservative members of the organization attached high importance to the role of emigration in preserving Lithuanian identity and efforts to liberate Lithuania. They also raised the importance of the country in the life of nation. M. Krupavièius, the leader of the conservative members, the national identity combined directly with the catholic identity and religious believes. Meanwhile Ateitininkai-modernists liberalised the cultural active participation of Lithuanian emigrants. They thought that creation of strong moral and cultural community in exile is more important for Lithuanian emigrants than to think of their own country. J. Girnius, the leader of this group, raised the idea that the loss of the fatherland can be compensated by stronger consciousness of Diaspora. This was actually realised through numerous cultural achievements, better understanding of national virtues. The sources of national consciousness were love and responsibility for their own nation. The programs to preserve national identity and retain against the denationalization, presented by M. Krupavièius and J. Girnius, were actually based on ethical values, such as responsibility, duty, guiltiness etc. The efforts made by ateitininkai to make NATIONAL identity stronger were very important for the creation of Lithuanian Diaspora. Despite certain facts that their ideological considerations sometimes contravened the practise of organisation or some of its members, ateitininkai were the vanguard of Lithuanian Diaspora in the Catholic community after the Second World War. They created a strong national identity that helped them to remain Lithuanians until the end of the cold war.